A study of grouped failure time data and the misapplication of recurrent event modeling. Issue 7 (9th August 2017) - Braschel, Melissa C.; Darlington, Gerarda A.; Klar, Neil
ABSTRACT: Clinical trials often assess whether or not subjects have a disease at predetermined follow-up times. When the response of interest is a recurrent event, a subject may respond at multiple follow-up times over the course of the study. Alternatively, when the response of interest is an irreversible event, a subject is typically only observed until the time at which the response is first detected. However, some recent studies have recorded subjects responses at follow-up times after an irreversible event is initially observed. This study compares how existing models perform when failure time data are treated as recurrent events.